UJI KUAT LENTUR PROFIL BAJA RINGAN GALVALUM TIPE C YANG DI GROUTING DENGAN VARIASI MORTAR - Fadhila Firdausa; Sri Rezki Artini; Ahmad Syapawi; Puryanto Puryanto (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2020)
Cold form steel is one type of material that is currently experiencing very rapid development. The advantages of the using cold form steel are so many, one of which is the light weight and high quality steel. This is an added value for cold form steel. But one of the weakness in cold form steel profile is the buckling effect. So that additional fillers are needed so that cold form steel has resistance with buckling effect. Mortar is a filler that is often used in construction. Therefore this research will be discuss the analysis of grouting mortar to prevent buckling effect in the cold form steel profile. And then the grouting mortar that will be used uses a variation of cement to sand as big as 1:1, 1:2, 1:3 and 1:4. From the results of the compressive strength of the mortar obtained compressive strength of 1: 1 has the greatest compressive strength of 30 Mpa. And then for the flexural test, the steel beam with mortar variation 1: 1 has the greatest resistance of 9558 Newton, with the smallest deflection value of 8 mm and the greatest stress of 19.47 Mpa, when compared to steel beams with variations of 1: 2, 1: 3, 1: 4 and steel beams without fillers.